HSV-1 and Alzheimer’s disease: more than a hypothesis - Piacentini, Roberto; De Chiara, Giovanna; Li Puma, Domenica D.; Ripoli, Cristian; Marcocci, Maria E.; Garaci, Enrico; Palamara, Anna T.; Grassi, Claudio (Frontiers in Pharmacology, 2014)
Among the multiple factors concurring to Alzheimer’s Disease (AD) pathogenesis, greater attention should be devoted to the role played by infectious agents. Growing epidemiological and experimental evidence suggests that recurrent herpes simplex virus type-1 (HSV-1) infection is a risk factor for AD although the underlying molecular and functional mechanisms have not been fully elucidated yet. Here, we review literature suggesting the involvement of HSV-1 infection in AD also briefly mentioning possible pharmacological implications of these findings.